ARRANGEMENT OF THE NATIONAL SYSTEMS OF REGULATORY IMPACT ASSESSMENT: EXPERIENCE OF RUSSIA, KAZAKHSTAN, AND UZBEKISTAN - Turgel, I.D.; Panzabekova, A.Zh.; Symaniuk, N.V. (Scientific Journal of Pedagogy and Economics, 2020)
The present research is aimed at comparative analysis of approaches to the arrangement of the national systems on the regulatory impact assessment in the post-Soviet countries – Russia, Kazakhstan, and Uzbekistan, revealing of existing problems in arranging the regulatory impact assessment in the mentioned countries, and formulating of the best practices in arranging the regulatory impact assessment to improve the activity and effectiveness of this institute. The results of the research can be used by the state governmental bodies of Russia, Kazakhstan, and Uzbekistan, supranational structures of the Eurasian Economic Union to justify the most effective ways of adoption and implementation of the managerial decisions in the field of regulatory policy, to enhance the transparency of the state policy in the post-Soviet countries, and forming of the effective interaction model of the state, business, and civil society. Following the research results, the prospective trends of the national systems of the regulatory impact assessment development are suggested.